A novel imaging method (FIM-ID) reveals that myofibrillogenesis plays a major role in the mechanically induced growth of skeletal muscle - Jorgenson, Kent W; Hibbert, Jamie E; Sayed, Ramy KA; Lange, Anthony N; Godwin, Joshua S; Mesquita, Paulo HC; Ruple, Bradley A; McIntosh, Mason C; Kavazis, Andreas N; Roberts, Michael D; Hornberger, Troy A (eLife, 2024)
An increase in mechanical loading, such as that which occurs during resistance exercise, induces radial growth of muscle fibers (i.e. an increase in cross-sectional area). Muscle fibers are largely composed of myofibrils, but whether radial growth is mediated by an increase in the size of the myofibrils (i.e. myofibril hypertrophy) and/or the number of myofibrils (i.e. myofibrillogenesis) is not known. Electron microscopy (EM) can provide images with the level of resolution that is needed to address this question, but the acquisition and subsequent analysis of EM images is a time- and cost-intensive process. To overcome this, we developed a novel method for visualizing myofibrils with a standard fluorescence microscope (fluorescence imaging of myofibrils with image deconvolution [FIM-ID]). Images from FIM-ID have a high degree of resolution and contrast, and these properties enabled us to develop pipelines for automated measurements of myofibril size and number. After extensively validating the automated measurements, we used both mouse and human models of increased mechanical loading to discover that the radial growth of muscle fibers is largely mediated by myofibrillogenesis. Collectively, the outcomes of this study offer insight into a fundamentally important topic in the field of muscle growth and provide future investigators with a time- and cost-effective means to study it.
Keywords: hypertrophy; exercise; growth; skeletal muscle; ultrastructure; myofibril